35th Himalayan-Karakoram-Tibet Workshop (HKT) “Geosciences for People’s Prosperity and Sustainable Development” November 02-04, 2022 (Journal of Nepal Geological Society, 2022)
This is the full volume of the Abstracts from the 35th Himalayan-Karakoram-Tibet Workshop (HKT) on “Geosciences for People’s Prosperity and Sustainable Development” November 02-04, 2022, Pokhara, Nepal.